VD_FINDINFO HC / 2014 / 462 vom 16. Mai 2014 - VD Tribunal cantonal (2014)
ASSISTANCE JUDICIAIRE, DÉNUEMENT, PERSONNE MORALE, REJET DE LA DEMANDE, SOCIÉTÉ À RESPONSABILITÉ LIMITÉE | 117 let. a CPC (CH)